Evangelicals and Abolitionist Methodologies - Andrea Smith (Religions, 2022)
The development of the primarily women-of-color-led movement for transformative justice has also shed light on the fact that abolition requires not just the transformation of social relations and place, but the transformations of subjectivity itself. This movement recognizes that violence is not just enacted against oppressed communities but is enacted with them, and hence the line between those who harm and those who face harm is often illusory. The movement for transformative justice—for accountability without disposability—calls on us to create different systems of relationality, which, in turn, transform who we think we are as people. Essentially, we are required to embark on an uncharted journey that will result in the creation of new selves we would not now recognize. Abolition can be seen as a process and a methodology rather than a presumed destination. To identify abolitionist methodologies, it can be helpful to look at unexpected places rather than presume that some spaces and peoples are necessarily more abolitionist than others. Consequently, this essay will look at abolitionism in an unexpected place, Christian evangelicalism.